Equity in Household Food and Packaging Waste Management: A Systematic Literature Review of Determinants, Service Design, Measurement Bias, and Inclusive Interventions - Abdurrahman Assel; Fitriyane Lihawa; Dewi Wahyuni K Baderan (Westscience Press, 2025)
Household food and packaging waste sit at the intersection of everyday routines and municipal service systems. Equity problems emerge when participation costs such as time, distance, storage space, and digital requirements are unevenly distributed across households. This systematic literature review synthesizes 55 Scopus-indexed journal articles published between 2020 and 2025, screened and reported using PRISMA 2020. We organize the evidence into four themes: equity determinants (gendered household labor, education-related competencies, and digital connectivity), service design mediators (coverage, proximity, pickup reliability, cleanliness, and rule clarity), measurement and bias in household waste quantification (self-report, diaries, weighing, composition audits, and smart sensing), and equity performance of packaging-oriented instruments (pay-as-you-throw pricing, deposit-return systems, extended producer responsibility, and refill or reuse models). Across contexts, equity effects are conditional on access: service reliability and convenience often explain intention-behavior gaps more than attitudes alone. Self-report methods frequently underestimate waste and overstate pro-environmental practices, while high-burden protocols risk excluding time-constrained households and biasing subgroup comparisons. We conclude with an access-first implementation roadmap and an equity-credible evaluation checklist combining affordability safeguards, low-technology participation pathways, and mixed-method measurement designs.